URINALYSIS AS PREDICTOR OF UPPER-TRACT URINARY STONE ON COLIC PAIN PATIENTS: SINGLE-CENTER COHORT STUDY - Wibowo, Edi; Satyagraha, Paksi; Daryanto, Besut (Indonesian Urological Association, 2022)
Objective: There was no study in our country especially in our hospital that studied correlation between urinalysis and upper tract urinary stone on colic pain patients, so we conducted the study. Material & Methods: We_collected patients' data with colic abdomen from January 2018 to January 2020 then divided into hematuria and non-hematuria group respectively. We excluded patients with lower-tract urinary stones, DJ-stent insitu, BPH, and malignancy. All patients had urinalysis and abdominal ultrasound, then continued with non-contrast abdominal CT-Scan or Intravenous Urography. Retrospective and prospective cohort study was performed to collect data: age, sex, serum ureum and creatinine, urinalysis results (pH, specific gravity, nitric, leucocyte, erythrocyte, crystal, and bacteria), stone number, site, and size, then analysed the relationship between urinalysis results with upper-tract urinary stone incidence using point biserial correlation. Results: We found 235 colic patients, 115 and 120 patients in hematuria and non-hematuria group respectively. Male patients were higher, 137_(58.3%). The highest incidence was in the range 41-50 years-old_(30.6%), mean 46.5313,53 years-old. Stone incidence was 55.7% in all colic patients. Stone was proven 78.3% and 34.2% in hematuria and non-hematuria group respectively. There was significant association between upper-tract urinary stone and haematuria compared to non-haematuria patients (p<0.05). Relative-risk (RR) was 2.29, CI_95%. Conclusion: Hematuria increases two-folds probability of upper-tract urinary stone. It is necessary to expand population data and follow-up center to make this representative